Geoquímica del rubidio-estroncio y edad de las esmeraldas colombianas (2000)
The rubidium-strontium method has been worked to determine the age of some colombian emeralds. These emeralds have low radiogenic strontium enrichments because of their younger age and their low rubidium content; they also have relatively high primary strontium content. Although the age of the emeralds of geologically younger formations is more difficult to establish, isotope values of these emeralds plotted on a graph of 87Sr/86Sr vs 87Rb/86Sr is indicative of about 61 to 67 million years as the age of mineralization.